PENYULUHAN PENCEGAHAN BAHAYA NARKOBA TERHADAP ANAK-ANAK USIA DINI - Yuli Andriansyah; Lalu Abdurrahman (UII, 2013)
Drug abuse can impair mental development of young generation for both the userand others. Drug as a substance that is necessary for the treatment in the health serviceis often abused are not in accordance with the standards of treatment and ifaccompanied by illicit drug trafficking will lead to a result which is very detrimental toindividuals and society, especially the younger generation may even pose a great dangerto the lives and values nation's cultural valueswhich in turn will undermine nationalsecurity. From a legal perspective, Narcotics are very dangerous for muda.Parageneration of children and young couple need guidance and knowledge about thedangers of drugs so as not to wear and fall in the world. From the implementation ofservice programs performed masyarakart teenage children enthusiastically participated inoutreach programs dangers of drug abuse prevention, so that teenagers understand theharmful effects that would occur if the consumption of drugs. Furthermore, teenagerscan find out the types of drugs that are very dangerous. As well, Marijuana, Heroin,Ecstasy.